Economic valuation for improved conservation among communities of Yankari Game Reserve, Nigeria - Ibrahim, Muhammad Sanusi (2017)
Yankari Game Reserve (YGR) is situated at Alkaleri local government area of Bauchi state, Nigeria. The conservation of the reserve is a unique one because of its national and international significance and also the role it plays to both tourist and the surrounding environment of the state. Among the most important functions the reserve plays, the game reserve serve as a biological hotspot to about 50 species of mammals, over 350 bird species and many species of plants. Moreover, it also plays different roles such as ecological, environmental, educational, economic and social role not only to the communities but the country at large. Despite its numerous importance, the reserve is increasingly facing threats and challenges at various degrees of non-sustainable human activities. Such activities range from poaching, deforestation, over grazing, pollution of water bodies and agricultural encroachment. The major reason for this excessive depletion was lack of valuation or underestimation of non-market values of the reserve resources, hence the need for effective valuation of the ecosystem resources. Therefore, estimates the economic values of YGR as an important hotspot for ecosystem and also reveal such values to policy makers and the adjoining communities. Contingent Valuation Method (CVM) and Choice Experiment (CE) were the techniques employed in this study. A total 422 responses were elicited using stratified random sampling technique. The logit regression model was used to estimate the willingness-to-pay based on the specified bid amounts presented based on the hypothetical market to support the improve conservation of YGR. The estimated mean willingness-to-pay base on CVM result wasN2376.42 and aggregate value of N130,000,464, while that of CE was estimated at and N2413.39 and compensating surplus N132,024,882. The total net benefit was estimated to be N262,025,346. The result was positive and highly encouraging as the respondents shows willingness to participate in the improve conservation of the reserve. Therefore, we recommend for a special conservation fund (donation) for sustainable conservation.